Optical coherence tomography angiography findings in patients affected by giant cell arteritis, with and without ocular involvement: a pilot study - Vannozzi, Lorenzo; Nicolosi, Cristina; Vicini, Giulio; Bacherini, Daniela; Giattini, Dario; Urban, Maria Letizia; Palermo, Adalgisa; Malandrino, Danilo; Bello, Federica; Virgili, Gianni; Giansanti, Fabrizio (Frontiers in Medicine, 2024)
Purpose We evaluated the clinical features and retinal and disk perfusion characteristics by using optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA) in a subset of giant cell arteritis (GCA) patients who manifested anterior ischemic optic neuropathy (AION), in a subset of GCA patients without ocular involvement, and in a control group composed of healthy controls. Methods We performed an observational study on the eyes of GCA patients affected by arteritic AION both in acute and chronic phases, unaffected eyes of AION, eyes of GCA patients without ocular involvement, and in a control group of healthy eyes of healthy individuals. All patients underwent a complete ophthalmic examination and an OCT and OCTA of the macula and the disk. Results The study evaluated 10 eyes of GCA patients with AION (AION group), 8 unaffected eyes of GCA patients with AION in another eye (unaffected eyes of AION group), 16 eyes of GCA patients without ocular involvement (non-ocular group), and 22 eyes of healthy patients (healthy group). The ganglion cell complex (GCC) superior and inferior thicknesses were significantly lower in the AION group compared to the unaffected eyes of the AION group (p = 0.045 and p = 0.034, respectively). All OCTA vascular density parameters of the optic disk analyzed in this study (optic nerve head (ONH) whole, superior, inferior, radial peripapillary capillary plexus (RPCP) whole, superior, inferior, lamina cribrosa (LC) whole, superior, inferior) resulted significantly lower in the AION group compared to the unaffected eyes group (p < 0.05 for all the comparisons). The ONH whole and inferior were statistically higher in the healthy group in comparison to the group of GCA patients without ocular involvement (p = 0.008 and p = 0.006, respectively). The ONH inferior was also statistically higher in the unaffected eyes of the AION group in comparison to the non-ocular group (p = 0.045). Regarding the OCTA macular vessel density parameters, the superficial capillary plexus (SCP), whole and inner, were statistically lower in the AION group compared with the unaffected eyes of the AION group. Conclusion We found a profound vascular impairment in eyes affected by AION and areas of hypoperfusion in the eyes of patients with GCA without ocular involvement, good BCVA, and no clinically significant features. We hypothesized that these areas of lower vessel density might represent areas of subclinical hypoperfusion that cannot be detected ophthalmoscopically.